'Performance' as Cryptonymy : The Economy of Failure in Critical Theory - Čale, Morana (2014)
Since the appearance of the discipline, considerable self-refexive discussion has been dedicated by PS scholars to attempts at circumscribing its axial notion of performance, 'a fundamentally contested term' which 'is also an extraordinarily opportunistic one' (Roach). The article examines the semantic instability of the concept as depending on a kind of 'cryptonymy' (Abraham and Torok ; Derrida).
Projekt MZOS
ENG